Pelatihan Dasar Penunjang Artikel Melalui Optimalisasi Penggunaan Aplikasi Publish or Perish dan Mendeley - Sari, Dewi Agustin Pratama; Mahfirah, Titis Fatarina; Muliasari, Indah; Hidayat, Nurdin; Armeliza, Diah; Dhinanty, Raihanisa Dara; Putri, Rachma Amalia (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
The basic research support skills training program is part of an effort to support the Tri Dharma of Higher Education, where lecturers play a role in sharing their knowledge with the community. This program is conducted because lecturers have diverse needs related to skills that support article writing. The goal of the program we offer is to provide solutions for training participants to be more skilled in creating articles more efficiently with the optimal use of the Publish or Perish and Mendeley applications. The Publish or Perish application is a tool that can help researchers understand the extent to which research on their subject has been conducted. Meanwhile, the Mendeley application can assist researchers in citing more easily. The research results show that participants' knowledge of both applications has increased, and participants will use both applications in their future research. Therefore, this community service activity will contribute to the improvement of scientific article writing.